2012
DOI: 10.4018/ijsem.2012010105
|View full text |Cite
|
Sign up to set email alerts
|

Linear Programming in Agriculture

Abstract: In agriculture, the production structure of farms can be highly diversified to reduce risk and uncertainty related to unsealing the products. To determine the optimal structure of crops, different methods which take into account the income and expenditure of crops per hectare are used. As a result, the area of each crop is identified, so that, in combining them to derive maximum profit level. In this paper, linear programming method is used for optimizing profit, investigating whether, after applying the econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Crop management and distribution have gained significant interest in science in recent years. Since the 1980s, linear programming has been used in crop allocation problems in order to increase their economic yield [1,2,9,18]. Various programs/softwares like MATLAB and Lindo have been used for crop management [27].…”
Section: Introductionmentioning
confidence: 99%
“…Crop management and distribution have gained significant interest in science in recent years. Since the 1980s, linear programming has been used in crop allocation problems in order to increase their economic yield [1,2,9,18]. Various programs/softwares like MATLAB and Lindo have been used for crop management [27].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literatures reviewed here are articles that used linear programming decision support systems for crop mix and cropping pattern (65%) while the remaining are articles that employed linear programming to promote the performance of dairy farms, crop-livestock integration, land and water resource use, arable crops and fisheries enterprises, botanical farm, and other forms of land use with the aim of maximizing net income, maximizing gross income, improving food security, and enhancing livelihood performance. Outlined results suggested that using LP as decision making tool in agriculture provides maximum annual return (Sarker et al, 1997;Hassan et al, 2005;Fallah Shamsi, 2010;Mohamad and Said, 2011;Alabdulkader et al, 2012;Felix et al, 2013;Geta et al, 2013;Andreea and Adrian, 2013;Gadge et al, 2014;Mugabe et al, 2014;Buzuzi and Buzuzi, 2018;Muhammed Jaslam et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…As income depends on expenditure, determining the optimal structure of crops that minimize expenditure and maximize income per available land size is essential. Andreea and Adrian (2013) used the LP model aiming to assess the possible effect of the optimal structure of crops to minimize expenditure and maximize profit in Romania. Accordingly, linear programming based land use decision making resulted reduction of expenditure by 81% and enhancement of profit by 143%.…”
Section: Resultsmentioning
confidence: 99%